Análise da influência da texturização superficial em mancais hidrodinâmicos radiais - Nogueirão, Luiz Fellipe (2023)
The use of textured surfaces can be observed in several applications where an improvement of a certain characteristic of the product or process is sought, with the aim of changing the conditions of friction, wear, and lubricant. When it comes to hydrodynamic radial bearings, one way to analyze the involved tribological parameters is through the Reynolds equation. A literature review is conducted to identify static analysis methods for textured hydrodynamic radial bearings. A correlation between the types of boundary conditions is conducted with considerations regarding the phenomenon of cavitation, which proves to be necessary to be included in the analysis of textured bearings. The correlation is consistent with historical progress, which starts with conditions that do not include cavitation effects (Half-Sommerfeld/Gümbel conditions); evolving to conditions that included cavitation effects, but in an exaggerated way by not considering the conservation of mass in the oil film (Reynold’s/Swift-Stieber conditions); and finally resulting in the cavitation theory, which considers the conservation of mass, of Jakobsson-Flober-Olsson (JFO). A computational program capable of analyzing the influence of texturing in radial hydrodynamic bearings is elaborated, considering the effects of cavitation with conservation of mass. The routine is validated with results from the literature and commercial software. The limitation in the discretization of textures as a function of the applied mesh size is analyzed. Finally, a series of analyzes are conducted with different cases of distribution of textures on the bearing. It is concluded that texturing can be satisfactory or harmful to the load capacity of the bearing, depending on the textured region. The texturing of the bearing in the central region shows on all cases harmful, while texturing in the converging and diverging regions of the pressure field can bring higher values for the load capacity.